Visualization of Intuitionistic Fuzzy B-Spline Space Curve and Its Properties - Zulkifly, Mohammad Izat Emir; Wahab, Abdul Fatah (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
In this paper, an intuitionistic fuzzy B-spline space curve is defined and some of its properties is introduced. Firstly, intuitionistic fuzzy control point is defined based on intuitionistic fuzzy and geometrical modeling concepts. Each of the control point relation that consists of three function is find and shown. Later, the control point is blended with B-spline basis function and intuitionistic fuzzy B-spline curve is visualized. Some of the control point and space curve properties in the Euclidean space is also discussed throughout this paper.